THE INFLUENCE OF ONLINE CUSTOMER REVIEWS AND PROMOTIONS ON PURCHASE DECISIONS OF GEN-Z USERS OF THE SHOPEE MARKETPLACE - Achmad Agil Agus; Gazali Amin; Dian Nirmasari (Jurnal Manajemen Dan Bisnis, 2024)
This study aims to determine the influence of Online Customer Review and promotion on the purchase decision of active students of the Faculty of Economics and Business, Ichsan Sidrap University who use the Shopee marketplace. The focus of the research includes how customer reviews and promotions such as "free shipping" affect students' decisions to buy products on Shopee. The method used is quantitative with an associative approach, which aims to identify the relationship between two or more variables. Primary data were collected through a questionnaire distributed to active students of the Faculty of Economics and Business, Universitas Ichsan Sidrap, class of 2021. The sample size of 51 respondents was determined using the Slovin formula with a 10% margin of error. The results of the study showed that Online Customer Reviews had a partially significant effect on purchase decisions, while promotions did not have a significant influence partially. Simultaneously, Online Customer Reviews and promotions together have a significant effect on purchasing decisions. The regression model used has an R-Square value of 0,435, which means that 43.5% of purchase decisions can be explained by these two variables. These findings reinforce the importance of customer reviews as the main consideration for consumers in making online purchases, especially among college students. This research makes a theoretical contribution to the study of digital consumer behavior and can be a strategic reference for e-commerce business people in designing more effective marketing strategies..